Prevalence and distribution of tobacco intake in various districts of the union territory of Ladakh, India - Malvika Singh; Manju Jamwal (Wolters Kluwer Medknow Publications, 2022)
Background: India is one of the top three tobacco burden countries in the world. Tobacco intake causes loss of health and environment and increases financial burden of an individual. Aims: The aim of this study was to assess the prevalence and distribution of tobacco intake among individuals of more than 15 years of age in the union territory of Ladakh, India. Subjects and Methods: District-wise data from National Health Survey-5, Ministry of Health and Family welfare 2019-2020, were collected, analyzed, and measured. Data collected were entered and statistically analyzed using the Statistical Package for the Social Sciences version 24.0 software (IBM, Armonk, NY, USA). Various districts were diagrammatically color coded and described. Results: Out of all the districts in the union territory of Ladakh, the prevalence of tobacco smoking was highest in Leh district and lowest in Kargil district. Conclusions: People should be made more aware of the ill effects of tobacco usage. Although the Government of India enacted various legislations to control tobacco use, its reduction lies in our hands and the same should be discussed with general masses by making them aware of the menace of tobacco on the mental, environmental, and health of an individual.